Separation anxiety, adjustment and loss experiences among Overseas Filipino Workers - Rogelio Jr Quiroga (International Review of Social Sciences Research)
Overseas Filipino Workers (OFWs) played a crucial role in global labor markets, contributing significantly to the economic development of their homeland while facing unique challenges abroad. This study examines the emotional experiences of OFWs in Japan, focusing on separation anxiety, adjustment, and loss experiences. Grounded on the frameworks of Attachment theory, this research explores how OFWs navigate the psychological challenges of living and working abroad. Using a qualitative phenomenological approach, three purposively selected OFWs participated in in-depth interviews. Thematic analysis was employed to identify patterns in their experiences, revealing common struggles such as homesickness, cultural adaptation difficulties, and emotional distress due to familial separation and personal losses. Despite these challenges, participants demonstrated resilience through coping mechanisms such as maintaining strong family connections, engaging in peer support networks, and developing adaptive strategies for workplace and cultural integration. The findings highlight the need for targeted interventions, including psychosocial support programs, culturally sensitive mental health services, and initiatives that strengthen family communication. These insights contribute to a deeper understanding of the emotional well-being of OFWs and inform policies and programs aimed at enhancing their psychological resilience and overall quality of life.